2020
DOI: 10.1155/2020/3605153
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hataedock Treatment on Epidermal Structure Maintenance through Intervention in the Endocannabinoid System

Abstract: The aim of this study was to investigate the efficacy of Hataedock (HTD) on skin barrier maintenance through the endocannabinoid system (ECS) intervention in Dermatophagoides farinae-induced atopic dermatitis (AD) NC/Nga mice. Douchi (fermented Glycine max Merr.) extracts prepared for HTD were orally administered to NC/Nga mice at a 20 mg/kg dose. Then, Dermatophagoides farinae extract (DfE) was applied to induce AD-like skin lesions during the 4th–6th and 8th–10th weeks. Changes in the epidermal structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…3Hb is the core ingredient used in the Hataedock treatment. Previous studies [10][11][12][13][14][15][16] have shown the effectiveness of alleviating AD by maintaining the lipid barrier through the use of 3Hb extract. Therefore, we assumed that the use of the 3Hb extract would work as a "proactive therapy" that could be administered prophylactically prior to the presentation of symptoms, and which could aid in suppressing a subsequent series of processes, by maintaining the lipid barrier through the recovery of FLG.…”
Section: Discussionmentioning
confidence: 99%
“…3Hb is the core ingredient used in the Hataedock treatment. Previous studies [10][11][12][13][14][15][16] have shown the effectiveness of alleviating AD by maintaining the lipid barrier through the use of 3Hb extract. Therefore, we assumed that the use of the 3Hb extract would work as a "proactive therapy" that could be administered prophylactically prior to the presentation of symptoms, and which could aid in suppressing a subsequent series of processes, by maintaining the lipid barrier through the recovery of FLG.…”
Section: Discussionmentioning
confidence: 99%